1991
DOI: 10.1177/074873049100600401
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Model for the Effects of Mutations and Temperature on Period and Phase Resetting of the Neurospora Circadian Oscillator

Abstract: This paper analyzes published and unpublished data on phase resetting of the circadian oscillator in the fungus Neurospora crassa and demonstrates a correlation between period and resetting behavior in several mutants with altered periods: As the period increases, the apparent sensitivity to resetting by light and by cycloheximide decreases. Sensitivity to resetting by temperature pulses may also decrease. We suggest that these mutations affect the amplitude of the oscillator and that a change in amplitude is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
1
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 37 publications
8
96
1
1
Order By: Relevance
“…90 It has been reported that reduced amplitude of circadian oscillators can increase the efficacy of perturbing agents such as light and other stimuli in causing phase shifts in various organisms. 89,[91][92][93] Although the observed reduction in the amplitude of circadian gene expression in BPI was subtle and only showed a trend for significance after correction for multiple comparisons, it is possible that the core clocks in bipolar patients are more vulnerable to external stimulation, which may contribute to unstable or more variable circadian rhythms as have been observed in bipolar patients. 13,94,95 Alterations in the overall expression level of core clock genes and clock-controlled genes can lead to anomalies in the circadian rhythmicity.…”
Section: Discussionmentioning
confidence: 98%
“…90 It has been reported that reduced amplitude of circadian oscillators can increase the efficacy of perturbing agents such as light and other stimuli in causing phase shifts in various organisms. 89,[91][92][93] Although the observed reduction in the amplitude of circadian gene expression in BPI was subtle and only showed a trend for significance after correction for multiple comparisons, it is possible that the core clocks in bipolar patients are more vulnerable to external stimulation, which may contribute to unstable or more variable circadian rhythms as have been observed in bipolar patients. 13,94,95 Alterations in the overall expression level of core clock genes and clock-controlled genes can lead to anomalies in the circadian rhythmicity.…”
Section: Discussionmentioning
confidence: 98%
“…al. (4) and later in more detail by Hatakeyama and Kaneko (7,8). Here we present a specific manifestation of this mechanism at the level of individual hexamers.…”
Section: Introductionmentioning
confidence: 57%
“…This is a clear signature of another mechanism of period robustness: at higher phosphorylation rates, corresponding to higher α ATP , the rate at which a system goes through state space increases, yet the length of one cycle also increases (4,8). It is important to note that the phenomenon of the variation of the phosphorylation cycle with the bulk ATP level emerges as a prediction of the Paijmans model; we did not deliberately design the model to have this property.…”
Section: Van Zon and Rust Models Only Show Strong Entrainability At Ementioning
confidence: 99%
See 1 more Smart Citation
“…Although molecular and theoretical explanations for many aspects of circadian oscillators have been developed over the past decade [6], there have been few attempts to describe temperature compensation on a mathematical kinetic basis [26]. For an overview on other or related attempts to explain temperature compensation the reader is referred to the following papers [12,13,[15][16][17][18]27,28]. However, a discussion of these various approaches on how to "balance P" is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%